PENGARUH STRUKTUR KEPEMILIKAN, EFEKTIVITAS KOMITE AUDIT, DAN KUALITAS AUDIT TERHADAP LUAS PENGUNGKAPAN KOMPENSASI MANAJEMEN KUNCI DALAM LAPORAN KEUANGAN (STUDI EMPIRIS PADA PERUSAHAAN SEKTOR PERDAGANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2015 S.D. 2017) - Fazil, Muhammad; Nadirsyah, Nadirsyah (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2019)
This study aims to investigate the effect of institutional ownership, managerial ownership, audit committee effectiveness, and audit quality both simultaneously and partially on the disclosures of key management compensation in financial statements. The test employed in this research is hypotheses while the data applied is secondary in the form of company financial and annual reports obtained from the official website of the Indonesia Stock Exchange and the official pages of each company that is analyzed using multiple linear regression analysis. The sampling method used is purposive sampling method with population of 61 companies listed in Indonesian Stock Exchange for the period 2015 until 2017 and sample of 41 companies. The results of this study indicate that institutional ownership, managerial ownership, audit committee effectiveness, and audit quality simultaneously have a significant and positive effect on the disclosures of key management compensation in financial statements. Furthermore, institutional ownership, audit committee effectiveness, and audit quality partially have a significant and positive effect for the disclosure of key management compensation, while managerial ownership partially does not have a significant effect on the disclosures of key management compensation in financial statements